OPTIMIZATION OF METAL NANOPARTICLES CONCENTRATION INTO DYE SOLUTION TO ENHANCE PERFORMANCE OF DYE SENSITIZED SOLAR CELLS - Rahayu, Setiya
Dye-sensitized solar cell (DSSC) is the third generation of solar cells that are quite promising in terms of fabrication and performance in comparison to conventional silicon-based solar cells that have been previously developed. The advantages of DSSC include the materials used are low-cost, the fabrication can be carried out at room temperature, and the technology is environmentally friendly. Starting from the research of O'Regan and Gratzel in 1991, many studies have been done in the detailed characteristics of the DSSC structure in an effort to further improve the performance of the device. One of the focus in DSSC research is the absorption of photons in dye molecules that enter into mesoporous layer of TiO2. Recent studies have shown that the addition of metal nanoparticles such as gold and silver (AuNP and AgNP) into the structure of the DSSC device can increase the absorption of light (photons) in the presence of the localized surface plasmon resonance (LSPR) effect of metal nanoparticles. In this study, AuNP and AgNP have been successfully added into dye solution which aim to increase the absorption of light that occurs in the dye layer of DSSC’s structure. Each nanoparticle that has been capped with organic molecules (oleylamine and octanethiol) is mixed with dye solution of type N-719 and then the optimization of concentration ratio between dye and metal nanoparticles involved is carried out. The characterization of the DSSC active material was carried out by means of UV-Vis and FTIR spectroscopy, while the surface morphology was characterized by TEM and SEM. The performance of the DSSC device fabrication results was carried out by measuring J-V using a solar simulator with an intensity of 100mW/cm2 . The fabrication results show enhancement in current density and efficiency when metal nanoparticles are added into the N-719 dye layer at a certain concentration range of metal nanoparticles. The addition of gold nanoparticles with Oleylamine (AuOA) capping showed optimum results at a concentration of 125µL with a value of Jsc 12.63 mA/cm2 and the Voc associated with the device efficiency of 4.54% which is greater 34.7 % in comparison to the reference device. Meanwhile on the DSSC device with the addition of silver nanoparticles capped with octanethiol (AgSC8) at a concentration of 175µL showed the value of Jsc 12.46 mA/cm2 and Voc 0.71 V with an efficiency result of 4.85% which is greater 43.9% than the reference device. The results of the performance of the DSSC device show the important role of metal nanoparticles, either AuNP or AgNP in a certain concentration range to increase photon absorbance associated with an increase in the value of the current density Jsc.